2021
DOI: 10.1080/10717544.2020.1870584
|View full text |Cite
|
Sign up to set email alerts
|

RPE-derived exosomes rescue the photoreceptors during retina degeneration: an intraocular approach to deliver exosomes into the subretinal space

Abstract: Retinal degeneration (RD) refers to a group of blinding retinopathies leading to the progressive photoreceptor demise and vision loss. Treatments against this debilitating disease are urgently needed. Intraocular delivery of exosomes represents an innovative therapeutic strategy against RD. In this study, we aimed to determine whether the subretinal delivery of RPE-derived exosomes (RPE-Exos) can prevent the photoreceptor death in RD. RD was induced in C57BL6 mice by MNU administration. These MNU administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 62 publications
2
9
0
Order By: Relevance
“…Interestingly, Chen et al (2021b) found that hRPC-exos had better efficacy in preventing temporal ONL thinning compared to nasal. hRPC-exos also induced downregulation of BAX and Caspase 3 but increased BCL-2, which is consistent with results from Wang et al on ARPE-exos (Wang et al, 2021). A finding unique to this article was that an in vitro co-culture showed hRPC-exos co-localized with human microglial cell line HMC3 and significantly reduced protein and gene levels of inflammatory proteins, which may be yet another mechanism of exosomes.…”
Section: Exosome/ev Therapy In Royal College Of Surgeon Rat Modelsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, Chen et al (2021b) found that hRPC-exos had better efficacy in preventing temporal ONL thinning compared to nasal. hRPC-exos also induced downregulation of BAX and Caspase 3 but increased BCL-2, which is consistent with results from Wang et al on ARPE-exos (Wang et al, 2021). A finding unique to this article was that an in vitro co-culture showed hRPC-exos co-localized with human microglial cell line HMC3 and significantly reduced protein and gene levels of inflammatory proteins, which may be yet another mechanism of exosomes.…”
Section: Exosome/ev Therapy In Royal College Of Surgeon Rat Modelsupporting
confidence: 91%
“…Both papers found that exosome treatment significantly preserved ONL thickness and scotopic ERG amplitudes of alpha and beta waves, retained normal retinal architecture and protected cone photoreceptors as shown in immunohistochemical staining (Wang et al, 2021) and TUNEL analysis (Deng et al, 2021). Furthermore, Wang et al (2021) also showed copious punctate and opsin staining in the retina which indicated cone photoreceptors were undamaged, with M & S cones best protected against MNU-induced injury, whereas no staining was found in the untreated MNU control group. Visual acuity, contrast sensitivity, and optokinetic behaviors tests displayed all-round protection of visual functions from ARPE-exo treatment which was not previously shown.…”
Section: Exosome/ev Therapy In Mnu Mouse/rat Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…RPE-derived exosomes (RPE-Exos) have also shown promising results in the treatment of RP. Recently, in C57BL6 mice with N-methyl-N-nitrosourea (MNU)-induced retinal detachment, it was shown that RPE-Exo treatment restores visual function by rescuing photoreceptor cells, significantly lowering TNFα and ILβ mRNA expression and inhibiting apoptosis pathway activation [ 231 ]. Similarly, MSC-Exos administration was shown to inhibit apoptosis induced by MNU and block retinal degeneration through the upregulation of miR-21 involved in key regulatory pathways [ 232 , 233 ].…”
Section: Novel Therapeutic Targets In Preclinical Phase: Exosomesmentioning
confidence: 99%
“…RPE cells can secrete exosomes in a paracrine manner to interfere with neighboring cells. Furthermore, the pathological process of eye diseases could be influenced by exosomes delivered via intranasal, intraocular, intravenous, and other mechanisms [ 4 ]. The role of RPE-derived exosomes in a potentially harmful oxidative response has been well established under photooxidative blue-light stimulation conditions [ 5 ].…”
Section: Introductionmentioning
confidence: 99%